Search for Vector Charmonium(-Like) States in the e+e-→ηJ/ψ Line Shape - Jielei Zhang; Rumin Wang (Advances in High Energy Physics)
The cross section of e+e-→ηJ/ψ has been measured by BESIII and Belle experiments. Fit to the e+e-→ηJ/ψ line shape, the resonant structures are evident. The parameters for the three resonant structures are M1=(3980±17±7) MeV/c2, Γ1=(104±32±13) MeV; M2=(4219±5±4) MeV/c2, Γ2=(63±9±3) MeV; and M3=(4401±12±4) MeV/c2, Γ3=(49±19±4) MeV, where the first uncertainties are statistical and the second are systematic. We attribute the three structures to ψ(4040), Y(4220), and ψ(4415) states. The branching fractions B(ψ(4040)→ηJ/ψ) and B(ψ(4415)→ηJ/ψ) are given. If Y(4220) is taken as ψ(4S) state, the branching fraction B(ψ(4S)→ηJ/ψ) is also given. Combining all Y(4220) parameters obtained from different decays, we give average parameters for Y(4220), which are MY(4220)=(4220.8±2.4) MeV/c2, ΓY(4220)=(54.8±3.3) MeV.